Evaluasi Teknis Penambangan Bauksit dari Front Penambangan Menuju Washing Plant Area untuk Menganalisis Faktor Ketidaktercapaian Target Produksi Berdasarkan Efisiensi Biaya Operasional Penambangan PT. ANTAM Tbk. UBPB Tayan, Kalimantan Barat - Rika Yastavia; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. ANTAM Tbk. UBPB Tayan, West Kalimantan undertake mining activities at Bukit 7B area by doing two activities in the process of transporting material to washing plant area. In this area ore which mined from front area will be transported to stockyard ETO (Exportable Transit Ore), then from a stockyard ETO ore is transported to the washing plant area. But due to the buildup of material in stockyrad ETO area, the company does the initiative by conducting a direct feeding (ore mined from front area will be transported directly to the washing plant area without doing stock in stockyard ETO area). Based on field observations, production target at Bukit 7B area PT. ANTAM Tbk. UBPB Tayan still has not achieved, from the results of the calculation obtained the actual production of work Activity 1 is 305,554.15 tons/month, while in work activity 2 of 190,004.75 tons/month. The operational cost used by the company in work Activity 1 is Rp. 195.167, 92X, while the operational cost of work activity 2 is Rp. 167.142, 22X. When the North West Corner Rule Transportation method is used, the minimum operational cost that the company can use is Rp. 184.420,83X. In other words, the North West corner rule method on this research proved to be very influential and helpful in the efficient or minimising costs.Keywords: Bauxite, Productivity, Excavator, Dump Truck, and North West Corner Rule Method